2002
DOI: 10.5194/angeo-20-405-2002
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated ground-based and Cluster observations of large amplitude global magnetospheric oscillations during a fast solar wind speed interval

Abstract: Abstract. We present magnetospheric observations of very large amplitude global scale ULF waves, from 9 and 10 December 2000 when the upstream solar wind speed exceeded 600 km/s. We characterise these ULF waves using groundbased magnetometer, radar and optical instrumentation on both the dawn and dusk flanks; we find evidence to support the hypothesis that discrete frequency field line resonances (FLRs) were being driven by magnetospheric waveguide modes. During the early part of this interval, Cluster was on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 61 publications
(68 reference statements)
2
50
0
Order By: Relevance
“…Sarafopoulos et al, 2001;Mann et al, 2002). However, in our study, we do not consider the Kelvin-Helmholz instability to be the cause of the observed surface waves and magnetopause oscillations since their occurrence characteristics did not suggest so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarafopoulos et al, 2001;Mann et al, 2002). However, in our study, we do not consider the Kelvin-Helmholz instability to be the cause of the observed surface waves and magnetopause oscillations since their occurrence characteristics did not suggest so.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, reconnection was ruled out and it was concluded that the K-H instability was the most likely excitation mechanism (Sarafoupoulos et al, 2001;Mann et al, 2002;Pitout et al, 2003). The rationale to rule out reconnection is that these observations were either during northward IMF, which does not favor reconnection, or during high-speed solar wind which favors the K-H instability.…”
Section: Introductionmentioning
confidence: 99%
“…Internal excitation mechanisms can involve resonance with energetic particle sources (e.g., Southwood et al, 1969), or coupling to fundamental plasma instabilities such as the drift-mirror mode (e.g., Pokhotelov et al, 1985Pokhotelov et al, , 1986Woch et al, 1988;. External FLR sources have been shown to be related to either solar wind discontinuity driven cavity/waveguide modes (e.g., Allan et al, 1986;Wright, 1994) or the Kelvin-Helmholtz instability on the magnetopause flanks (e.g., Southwood, 1974;Chen and Hasegawa, 1974;Southwood, 1985, 1986;Mann et al, 2002;Rae et al, 2005 -herein after referred to as R05). Many of these studies invoked a form of the magnetospheric waveguide in order to explain their results, where the magnetopause forms the outer boundary of the waveguide, and a strong gradient in the Alfvén speed forms the inner boundary for the compressional mode waves.…”
Section: Introductionmentioning
confidence: 99%
“…The waves are important because they are thought to cause momentum, energy, and perhaps mass transfer into the magnetosphere. They also may be a source of Pc 5 magnetospheric waves that are believed to energize trapped electrons [e.g., O'Brien and McPherron, 2003;Li and Temerin, 2001;Mann et al, 2002].…”
Section: Introductionmentioning
confidence: 99%